Lomustine-temozolomide combination therapy versus standard temozolomide therapy in patients with newly diagnosed glioblastoma with methylated MGMT promoter (CeTeG/NOA-09): a randomised, open-label, phase 3 trial - Herrlinger, Ulrich; Brehmer, Stefanie; Wick, Wolfgang (The lancet, 2019)
Background - There is an urgent need for more effective therapies for glioblastoma. Data from a previous unrandomised phase 2 trial suggested that lomustine-temozolomide plus radiotherapy might be superior to temozolomide chemoradiotherapy in newly diagnosed glioblastoma with methylation of the MGMT promoter. In the CeTeG/NOA-09 trial, we aimed to further investigate the effect of lomustine-temozolomide therapy in the setting of a randomised phase 3 trial. - Methods - In this open-label, randomised, phase 3 trial, we enrolled patients from 17 German university hospitals who were aged 18-70 years, with newly diagnosed glioblastoma with methylated MGMT promoter, and a Karnofsky Performance Score of 70% and higher. Patients were randomly assigned (1:1) with a predefined SAS-generated randomisation list to standard temozolomide chemoradiotherapy (75 mg/m2 per day concomitant to radiotherapy [59-60 Gy] followed by six courses of temozolomide 150-200 mg/m2 per day on the first 5 days of the 4-week course) or to up to six courses of lomustine (100 mg/m2 on day 1) plus temozolomide (100-200 mg/m2 per day on days 2-6 of the 6-week course) in addition to radiotherapy (59-60 Gy). Because of the different schedules, patients and physicians were not masked to treatment groups. The primary endpoint was overall survival in the modified intention-to-treat population, comprising all randomly assigned patients who started their allocated chemotherapy. The prespecified test for overall survival differences was a log-rank test stratified for centre and recursive partitioning analysis class. The trial is registered with ClinicalTrials.gov, number NCT01149109. - Findings - Between June 17, 2011, and April 8, 2014, 141 patients were randomly assigned to the treatment groups; 129 patients (63 in the temozolomide and 66 in the lomustine-temozolomide group) constituted the modified intention-to-treat population. Median overall survival was improved from 31·4 months (95% CI 27·7-47·1) with temozolomide to 48·1 months (32·6 months-not assessable) with lomustine-temozolomide (hazard ratio [HR] 0·60, 95% CI 0·35-1·03; p=0·0492 for log-rank analysis). A significant overall survival difference between groups was also found in a secondary analysis of the intention-to-treat population (n=141, HR 0·60, 95% CI 0·35-1·03; p=0·0432 for log-rank analysis). Adverse events of grade 3 or higher were observed in 32 (51%) of 63 patients in the temozolomide group and 39 (59%) of 66 patients in the lomustine-temozolomide group. There were no treatment-related deaths. - Interpretation - Our results suggest that lomustine-temozolomide chemotherapy might improve survival compared with temozolomide standard therapy in patients with newly diagnosed glioblastoma with methylated MGMT promoter. The findings should be interpreted with caution, owing to the small size of the trial. - Funding - German Federal Ministry of Education and Research.